2008
DOI: 10.1021/jo801212q
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Carbapenams via Kinugasa Reaction

Abstract: A facile approach to carbapenams via Kinugasa reaction between terminal copper acetylides and nonracemic cyclic nitrones derived from malic and tartaric acid is reported. The stereochemical preferences observed in these reactions are explained. The reaction provides an entry to the carbapenams basic skeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…3). 56 Similarly to additions involving nonchiral acetylenes, the initial 1,3-dipolar-cycloaddition step proceeds almost exclusively anti to the tert-butoxy Our group 69 demonstrated that certain acetylenes display enhanced reactivity in the investigated processes, providing corresponding 2-azetidinones in higher yield and therefore requiring a shorter reaction time ( Table 2, acetylenes ent-33 and 44).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 3 more Smart Citations
“…3). 56 Similarly to additions involving nonchiral acetylenes, the initial 1,3-dipolar-cycloaddition step proceeds almost exclusively anti to the tert-butoxy Our group 69 demonstrated that certain acetylenes display enhanced reactivity in the investigated processes, providing corresponding 2-azetidinones in higher yield and therefore requiring a shorter reaction time ( Table 2, acetylenes ent-33 and 44).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…49b Use of bulky amines usually directs the reaction toward the formation of kinetic cis-2-azetidinones. 55,56,57 Reactions are typically carried out in MeCN or DMF, since these solvents offer good solubility of copper acetylides. Tang and co-workers 55 performed detailed studies on all of these factors.…”
Section: Catalysts and Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many research groups [15][16][17][18][19][20] have been successfully developed synthetic strategies to perform catalytic enantioselective 1,3-dipolar cycloaddition reactions, which has afforded a reasonable synthetic process to perform the stereo-selective construction of heterocycles with congested stereogenic centers and heteroatom acyclic molecules followed by the subsequent reductive ring opening of the resulting cycloadducts. 21,22 To our knowledge, the most of 1, 3-dipole cycloaddition reaction of nitrone and subsequent transformation routinely were promoted by noble metal catalysts such as Pd, Pt, Au, In, and Ru, 23,24 inexpensive metal or metalfree as alternative catalyst were desired to catalyze this kind of organic reactions.…”
Section: Figure 1 Examples Of Significant Compounds Containing 4-amimentioning
confidence: 99%